A new species of Mictyris Latreille, 1806 (Crustacea: Decapoda: Brachyura: Mictyridae) from the Andaman coast of Thailand, with notes on its ecology and behaviour - Davie, Peter J.f.; Wisespongpand, Puntip; Shih, Hsi-Te (Zootaxa, 2013)
A new species of soldier crab (genus Mictyris Latreille, 1806) is described from the Andaman Sea coast of Thailand. Mictyris thailandensis sp. nov. differs morphologically from its described congeners by its pale plain colouring, the differently shaped apex of the male first gonopod, and by chela features. It also has significant genetic divergence (cytochrome oxidase I ≥ 11.95%) from other described species.